1998
DOI: 10.1046/j.1365-2567.1998.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Unresponsiveness of CD48+/− thymocytes to lectin stimulation in LEC mutant rats

Abstract: A mutant strain of rat, LEC, shows a novel arrest of T-cell maturation from CD4+8+ to CD4+8-, but not to CD4-8+ cells in the thymus. The responsible mutant locus is designated the thid, which was acted upon in a recessive manner of inheritance. We found that LEC rat thymocytes failed to respond to interleukin (IL)-1, IL-6 and IL-7 in the presence of the mitogenic lectins, Allo A or concanavalin A (Con A). The unresponsiveness appeared to be due to unresponsiveness to the lectin stimulation rather than because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A decrease in CD4 lineage T cells is a common phenotype seen in LEC rats (14) and themis-deficient mice, but a decrease in CD8 T cells is seen only in the themis-deficient mice. However, since the reduction of CD8 T cells in these mice is not as prominent as the CD4 T-cell defect, it is probable that this phenotype is masked in LEC rats through unknown compen- FIG.…”
Section: Vol 29 2009 Gene Essential For Single Positive Thymocytes mentioning
confidence: 95%
See 1 more Smart Citation
“…A decrease in CD4 lineage T cells is a common phenotype seen in LEC rats (14) and themis-deficient mice, but a decrease in CD8 T cells is seen only in the themis-deficient mice. However, since the reduction of CD8 T cells in these mice is not as prominent as the CD4 T-cell defect, it is probable that this phenotype is masked in LEC rats through unknown compen- FIG.…”
Section: Vol 29 2009 Gene Essential For Single Positive Thymocytes mentioning
confidence: 95%
“…5A). LEC rats are known to have a reduction in CD4 SP T cells in the thymus and periphery, resulting in a defective immune response, a phenotype designated thid (for T helper immunodeficiency), which is inherited in an autosomal recessive manner (14). Two independent studies reported that the large genomic deletion that eliminates ptpr and RGD1560849 (the rat analog of E430004N04Rik) function causes the thid phenotype.…”
Section: Vol 29 2009 Gene Essential For Single Positive Thymocytes mentioning
confidence: 99%
“…In addition, peripheral CD4 ϩ T cells of LEC rats were shown not to function as Th cells in Ab production against T cell-dependent Ag and IL-2 production by polyclonal stimulation (32,33). However, it remains unclear whether the T cell dysfunction of LEC rats might have an influence on any disease associated with the immune disorder.…”
mentioning
confidence: 99%